Generation of Bone Tissue Using Adipose Tissue-derived Stem Cells - Baygol, Emre Gonenc; Guneren, Ethem; Karaaltin, Mehmet Veli; Canter, Halil Ibrahim; Ozturk, Kahraman; Ovali, Ercument; Ozpur, Mustafa Aykut; Yildiz, Kemalettin; Eyuboglu, Fatma (BEZMIALEM VAKIF UNIV, 2021)
Objective: Bone grafts and even bone substitutes do not meet all of the requirements of bony reconstructions. The aim of this study was to generate bone tissue from autologous adipose tissue-derived mesenchymal stem cells (ATDMSCs) and decellularised bone allografts. Methods: A 1.5 cm bone defect developed in the middle third of the rabbit's ulna. Reconstructions were carried out using miniplate and screws and interpositional autogenous bone grafts according to the designs of the groups: (1) No touch, (2) cryopreserved, (3) decellularised and (4) ATDMSCs-implanted decellularised bones. Before implantation, ATDMSCs in the last group were labelled with Q-dot and identified microscopically. Results: Graft recovery and irregular callus formation were observed in the first, second and forth groups. In the first group, the organisation of Haversian systems, the structure of the lacunae and the presence of canaliculi ossiums were observed

in the second group, approximately 40\% of the Haversian canals contained blood vessels, and canaliculi ossiums in the form of thin filaments were found in 90\% of the microscopically examined areas

in the third group, most Haversian canals were empty, most osteocyte canals were devoid of cells, and canaliculi ossiums were absent

in the fourth group, some of the Haversian canals contained blood vessels, and there were partly lacunae containing cells due to decellularisation, whereas in approximately 50\% of the examined microscope areas, the presence of canaliculi ossiums with evidence of mesenchymal stem cells differentiated into osteocytes was demonstrated by Q-dot traced cells. Conclusion: In this study, the establishment of a proper niche environment for adipose-derived mesenchymal cells promotes their development into osteogenic cells.
Keywords: Tissue; stem cell; adipose; mesenchyme; regeneration